Co-pyrolysis of paper mill sludge and textile dyeing sludge with high calorific value solid waste: Pyrolysis kinetics, products distribution, and pollutants transformation. (1st December 2022) - Feng, Shenghao; Zhang, Guangxue; Yuan, Dingkun; Li, Yunchao; Zhou, Yifan; Lin, Fawei
Graphical abstract: Highlights: The quality of individual pyrolysis products of PMS and TDS is limited. Co-pyrolysis can reduce the pyrolysis activation energy. Co-pyrolysis promotes the organic degradation and reduces solid residues. Co-pyrolysis optimizes pyrolysis products, especially for pyrolysis liquid. Abstract: Paper mill sludge (PMS) and printing and textile dyeing sludge (TDS) are two typical industrial sludge with high calcium content, high ash content and low calorific value. To attain effective removal of industrial solid waste, in this study, PMS and TDS are first pyrolyzed independently to study their thermochemical behavior. Results show that 600 °C is the optimal pyrolysis temperature for both PMS and TDS from the perspective of organics degradation. However, the yield and quality of pyrolysis oil and gas are still at low level due to the characteristics of high ash content and low organic content, which is not suitable for fuel recovery. Two kinds of organic solid wastes with high calorific value, duckweed (DW) and waste tire (WT), are co-pyrolyzed with PMS and TDS, which can effectively reduce activation energy and increase the yield of liquid and gas products. The most prominent is P1D1 pyrolysis gas, the production of CH4 and C2 -C3 increased from 10.80 L/kg and 3.89 L/kg to 20.16 L/kg and 15.58 L/kg respectively, and the high calorific value also increased to 230.93 kJ/kg. The quality of pyrolysis liquid has been improved significantly as the declined N and O-heteroatom content (especially for P1D1 and T1W1) due to the inhibition effect of co-pyrolysis on the N/O migration into pyrolytic liquid. The solid residue from the co-pyrolysis of PMS and DW contains rich N -functional groups and can promote the conversion of pyridinic-N and pyrrolic-N to quaternary-N. Compared with independent pyrolysis, co-pyrolysis can promote the degradation of harmful organic matter in sludge. The addition of DW and WT co-pyrolysis reduced the solid residue yield of PMS by 19.9 wt% and 14.9 wt% (13.4 wt% and 10.5 wt% for TDS). This work provides inspiration for further understanding the safe disposal of PMS and TDS by pyrolysis.